2001
DOI: 10.5194/angeo-19-59-2001
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic-E associated with the Leonid meteor shower event of November 1998 over low and equatorial latitudes

Abstract: Abstract. Rapid radio soundings were made over Ahmedabad, a low latitude station during the period 16-20 November 1998 to study the sporadic-E layer associated with the Leonid shower activity using the KEL Aerospace digital ionosonde. Hourly ionograms for the period 11 November to 24 November were also examined during the years from 1994 to 1998. A distinct increase in sporadic-E layer occurrence is noticed on 17, 18 and 19 November from 1996 to 1998. The diurnal variations of f 0 E s and f b E s also show sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…The preferential detection of southwestward-directed, nighttime MSTIDs during E s has been seen before (see, e.g., Helmboldt, 2012;Cosgrove, 2013). Other authors have also demonstrated enhanced E s during heightened meteor activity (Chandra et al, 2001;Yellaiah et al, 2001). In addition, the results from the imaging of regions of backscatter from E s FAIs largely conforms with previous observations in the Caribbean (Hysell et al, 2004Larsen et al, 2007).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The preferential detection of southwestward-directed, nighttime MSTIDs during E s has been seen before (see, e.g., Helmboldt, 2012;Cosgrove, 2013). Other authors have also demonstrated enhanced E s during heightened meteor activity (Chandra et al, 2001;Yellaiah et al, 2001). In addition, the results from the imaging of regions of backscatter from E s FAIs largely conforms with previous observations in the Caribbean (Hysell et al, 2004Larsen et al, 2007).…”
Section: Discussionmentioning
confidence: 78%
“…Interestingly, some investigations found no observational evidence of a correlation between meteor activity and E s (e.g., Baggaley and Steel, 1984;Whitehead, 1989). However, some instances of positive correlation between E s and meteor activity have been observed (e.g., Haldoupis et al, 2007), and there is some indication that the occurrence of E s is enhanced during meteor showers (Chandra et al, 2001;Yellaiah et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have concluded that an increase in Es immediately follows the occurrence of meteor shower and others have inferred a delay in the increase, while some authors have found no correlation between meteor shower activity and the occurrence of Es (Malhotra et al, 2008;Maruyama et al, 2008). One possible reason for the confusion on the effects of meteor showers on Es activity is due to the difficulty in distinguishing between intense meteor echoes and the usual Es layers echoes on ionograms during meteor shower periods, which can be overcome to a certain extent by using rapidrun ionosondes and tracking echoes from every ionograms frame as done in recent years (Chandra et al, 2001;Maruyama et al, 2008). Moreover, ionospheric irregularities are generated due to plasma instabilities, which operate under certain basic condition in the ambient electric field, and other neutral and electrodynamical parameters.…”
Section: Discussionmentioning
confidence: 92%
“…Increases in the Es activity associated with meteor showers have been reported by many researchers. The Es layers associated with the Leonid meteor shower event of November 1998 has been reported on the basis of observations of rapid radio soundings in India (Chandra et al, 2001). During the Leonid meteor shower in 2001, long-duration Es echoes persisting for approximately 40 min were recorded on ionograms in Japan, which were attributed to the transient formation of a Es layer caused by a meteor ablation immediately overhead (Maruyama et al, 2003).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation